Implementation of a Blockchain-Based IDS for Cloud Infrastructure - Putrawan Hadi; M. Hidayaturrahman; Firmansyah (Universitas Islam Al-Azhar Mataram, 2025)
Data security in cloud computing environments has become a major concern as system architectures grow increasingly complex, distributed, and open to external access. One of the essential components in maintaining system security is the Intrusion Detection System (IDS), which is responsible for identifying suspicious activities and cyberattacks. However, traditional IDS implementations face several limitations, including the vulnerability of log integrity, limited scalability in dynamic cloud environments, and reliance on centralized architectures that are prone to single points of failure and internal threats. To address these challenges, the integration of blockchain technology into IDS has emerged as an innovative solution. Blockchain offers decentralization, transparency, and immutability of records, which are highly relevant for strengthening IDS reliability and trust.This study employs a literature review methodology by examining scholarly articles, academic journals, and real-world case studies focusingon blockchain-based IDS implementations within cloud computing infrastructure. The findings suggest that using blockchain—particularly permissioned frameworks such as Hyperledger Fabric—can significantly enhance the integrity of IDS logs, enable transparent and verifiable audit trails, and support secure multi-tenant collaboration in both public and private cloud settings. Furthermore, the combination with machine learning techniques, federated learning, and Zero Trust Architecture (ZTA) increases the detection accuracy and responsiveness of the system. Nevertheless, several challenges remain, including transaction efficiency, computational overhead, and system integration complexity. Therefore, a carefully designed and optimized architecture is required tomaximize the benefits of blockchain-based IDS in cloud environments.